2018
DOI: 10.1101/354233
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

STK25 directly activates LATS1/2 independent of MST/MAP4Ks

Abstract: The Hippo pathway maintains tissue homeostasis by negatively regulating the oncogenic transcriptional co-activators YAP and TAZ. Though functional inactivation of the Hippo pathway is common in tumors, mutations in core pathway components are rare. Thus, understanding how tumor cells inactivate Hippo signaling remains a key unresolved question.Here, we identify the kinase STK25 as a novel activator of Hippo signaling. We demonstrate that loss of STK25 promotes YAP/TAZ activation and enhanced cellular prolifera… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Highlighting the importance of YAP/TAZ regulation, previous studies have shown that LATS1/2 can be activated in an MST1/2‐independent way by mitogen‐activated protein kinase kinase kinase kinase 1–7 (MAP 4K1–7) 47 . These enzymes act by phosphorylating LATS1/2 in its hydrophobic motif 48 .…”
Section: Physiological Functions Of Yap/tazmentioning
confidence: 99%
See 1 more Smart Citation
“…Highlighting the importance of YAP/TAZ regulation, previous studies have shown that LATS1/2 can be activated in an MST1/2‐independent way by mitogen‐activated protein kinase kinase kinase kinase 1–7 (MAP 4K1–7) 47 . These enzymes act by phosphorylating LATS1/2 in its hydrophobic motif 48 .…”
Section: Physiological Functions Of Yap/tazmentioning
confidence: 99%
“…These enzymes act by phosphorylating LATS1/2 in its hydrophobic motif 48 . Moreover, the Serine/Threonine Kinase 25 (STK25) was also shown to activate LATS1/2 by direct phosphorylation of the activation loop motif 47 . The redundancy of enzymes which activate LATS1/2 and the different ways of its activation indicate LATS1/2 is a central regulator of YAP/TAZ activity that needs to be tightly regulated in order to maintain homeostasis and normal development.…”
Section: Physiological Functions Of Yap/tazmentioning
confidence: 99%